Adolescent pregnancies in the Amazon Basin of Ecuador: a rights and gender approach to adolescents’ sexual and reproductive health - Isabel Goicolea (Taylor & Francis Group, 2010)
In the Andean region of Latin America over one million adolescent girls get pregnant every year. Adolescent pregnancy (AP) has been associated with adverse health and social outcomes, but it has also been favorably viewed as a pathway to adulthood. AP can also be conceptualized as a marker of inequity, since it disproportionately affects girls from the poorest households and those who have not been able to attend school. Using results from a study carried out in the Amazon Basin of Ecuador, this paper explores APs and adolescents’ sexual and reproductive health from a rights and gender approach. The paper points out the main features of a rights and gender approach, and how it can be applied to explore Aps. Afterward it describes the methodologies (quantitative and qualitative) and main results of the study, framing the findings within the rights and gender approach. Finally, some implications that could be generalizable to global reserach on APs are highlighted. The application of the rights and gender framework to explore APs contributes to a more integral view of the issue. The rights and gender framework stresses the importance of the interaction between rights-holders and duty-bearers on the realization of sexual and reproductive rights, and acknowledges the importance of gender–power relations on sexual and reproductive decisions. A rights and gender approach could lead to more integral and constructive interventions, and it could also be useful when exploring other sexual and reproductive health matters.